Carbofuran Abrogates the Membrane Ca++-Atpase Activity in Liver: The Role of Cholesterol - C. Ghosh, Manik; Shukla, Hem; K. Ray, Arun (Journal of Proteomics and Genomics Research, 2014)
Carbofuran is a broad spectrum pesticide used in agricultural fields and domestic places throughout the world. It is one of the deadly toxic carbamate pesticide that kills the pest by inhibiting the crucial enzyme of nervous system known as acetyl cholinesterase. In the present study, we report how carbofuran increases the different spectrum of cholesterols, including free cholesterol and esterified cholesterol in the fish hepatocytes. It is observed that induced-cholesterol can inhibit the enzymatic activity such as Ca++-ATPase, which is a critical protein for maintaining the calcium homoeostasis in the cellular microenvironment. Carbofuran integrates into human body through foods and drinks. As trace of carbofuran is identified in our daily food and drinks, we examined the homology of Ca++-ATPase between the fish and human, so our data can illuminate the effects of carbofuran on this crucial enzyme. While studying the homology with the help of bioinformatics, we recognized that there is around 70% homology in the protein sequence of Ca++-ATPase between fish Heteropneustesfossilisand human (Homo sapiens), which appears as sufficient to simulate our fish-model data in human. This study demonstrates that carbofuran affects our day-to-day life by inhibiting Ca++-ATPase through modulation of lipid synthesis, a critical regulatory system that controls overall homeostasis in our body.
Keywords: Carbofuran; Fish; cholesterol; Ca++-ATPase; liver